2017
DOI: 10.5603/fhc.a2017.0010
|View full text |Cite
|
Sign up to set email alerts
|

The role of homocysteine in seminal vesicles remodeling in rat

Abstract: Increased plasma concentration of Hcy accompanied by the accumulation of collagen and upregulation of MMPs in rat seminal vesicles might contribute to the remodeling of seminal vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Our result is in agreement with those reported by many previous studies that showed a methionine-enriched diet to induce a moderate Hhcy in different animal models (pig, gerbil, and rat) [27,29,30]. In the rat, a species known to be athero-resistant administration of a high dose of methionine (200 mg/ kg) for a long period (6 months) is necessary to induce Hhcy [31,32]. In our laboratory, a study published in 2019, reported for the first time a moderate Hhcy in Psammomys obesus; however, the Hhcy was induced by a high dose of methionine (300 mg/kg) administered for 4 weeks [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result is in agreement with those reported by many previous studies that showed a methionine-enriched diet to induce a moderate Hhcy in different animal models (pig, gerbil, and rat) [27,29,30]. In the rat, a species known to be athero-resistant administration of a high dose of methionine (200 mg/ kg) for a long period (6 months) is necessary to induce Hhcy [31,32]. In our laboratory, a study published in 2019, reported for the first time a moderate Hhcy in Psammomys obesus; however, the Hhcy was induced by a high dose of methionine (300 mg/kg) administered for 4 weeks [13].…”
Section: Discussionsupporting
confidence: 93%
“…We first investigated the body weight of the animal every month during the 6 months of methionine administration and reported a significant decrease from the 2nd month to the end of the experiment. Similar results were reported by Ghoul and Zhou in rats and mice respectively [32,33]. However, the bodyweight seems to be not always affected in rats and gerbils by methionine-induced Hhcy [26,30,31] and it is plausible that the variations in the dose of methionine and duration of its administration may play a role.…”
Section: Discussionsupporting
confidence: 85%
“…[19][20][21] Several studies have found that HHcy is associated with the occurrence of fibrosis in different tissues of rats, such as myocardial fibrosis, intestinal fibrosis, and seminal vesicle fibrosis. [22][23][24] However, it is still unclear whether there is a similar association between HHcy and liver or LF. We conducted this crosssectional study to understand this correlation and found that Hcy was strongly correlated with the LSM values, as well as with the recognized serum biomarkers (AST/ ALT, APRI, FIB-4), used to evaluate the degree of LF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the content of fibrillar collagens in seminal vesicles was elevated in hyperhomocysteinemic rats. Hyperhomocysteinemia increased the expression of MMP-2, -3, -7 and -9 in seminal vesicles [ 185 ]. The accumulation of collagen and upregulation of MMPs in seminal vesicles might contribute to the physiological remodeling of seminal vesicles.…”
Section: Ev-associated Mmps: Roles In Immunosuppression and Reprodmentioning
confidence: 99%